The effect of dietary fiber supplement on prevention of gestational diabetes mellitus in women with pre-pregnancy overweight/obesity: A randomized controlled trial - Zhang, Dong-Yao; Cheng, De-Cui; Cao, Yan-Nan; Su, Yao; Chen, Li; Liu, Wen-Yu; Yu, Yue-Xin; Xu, Xian-Ming (Frontiers in Pharmacology, 2022)
Objective: To investigate the effect of dietary fiber intake during pregnancy on the prevention of gestational diabetes mellitus (GDM) in women who are overweight/obese prior to pregnancy. Methods: This randomized controlled trial was conducted in Shanghai General Hospital from June 2021 to March 2022. A total of 98 women who reported BMI≥24 kg/m2 prior to pregnancy were recruited before their 20th gestational week, and randomly (simple random allocation) assigned to the fiber supplement group (12 g of dietary fiber power twice daily) and the control group (standard prenatal care) from 20 to 24+6 gestational weeks. Both groups received nutrition education and dietary advice during the study. GDM diagnosis was performed by an oral glucose tolerance test (OGTT) at 25–28 weeks’ gestation. Data are presented as means with SD, as medians with IQR, or as counts with percentages as appropriate. Comparisons were conducted using a t-test, Mann-Whitney U test, and χ2 test, respectively. Results: The incidence of GDM was significantly reduced in the fiber supplement group compared with the control group: 8.3 vs. 24.0% (χ2 = 4.40, p = 0.036). At OGTT, the mean fasting plasma glucose in the fiber supplement group was significantly lower than before the intervention (4.57 ± 0.38 mmol/L vs. 4.41 ± 0.29 mmol/L, p < 0.01) but not in the control group (4.48 ± 0.42 mmol/L vs. 4.37 ± 0.58 mmol/L, p = 0.150). Compared with the control group, the TG and TG/HDL-C ratio levels in the intervention group were significantly higher than those in the control group (2.19 ± 0.54 mmol/L vs. 2.70 ± 0.82 mmol/L and 1.19 ± 0.49 vs.1.63 ± 0.63, respectively, all P＜0.05). The body weight gain was significantly lower in the fiber supplement group than the control group (1.99 ± 1.09 kg vs. 2.53 ± 1.20kg, p = 0.022). None of the women randomized to the fiber supplement group experienced preterm birth (<37 weeks gestation) compared with 12.0% in the control group (p = 0.040). Excessive weight gain (total weight gain >11.5 kg for overweight, and >9.0 kg for obesity) occurred in 46.7% of women in the fiber supplement group compared with 68.0% in the control group (p = 0.035). There were no differences in other maternal and neonatal outcomes. Conclusion: Increased dietary fiber intake in pregnant women who were overweight/obese prior to pregnancy may reduce the risk of GDM, excessive weight gain, and preterm birth, but it did not improve blood lipids.